Melampaui Kedirian Identitas Batak Melalui Ritual dan Sejarah Masyarakatnya Atas Inspirasi Levinas - Maria Anggreini Grace Kelly Habeahan; Ruth Florescia Simanjuntak; Rustono Farady Marta (JURNAL SIMBOLIKA: Research and Learning in Communication Study (E-Journal), 2020)
This study aims to determine the identity and selfhood of each Batak community towards the messages conveyed by their ancestors to be applied in the daily life of the Batak community. The research uses an interpretive paradigm, which views social reality as something dynamic, processed and full of subjective meaning. Social reality is nothing but a social construct. The author describes the Batak community's construction of the philosophy passed down from their ancestors in the life of individual relations with their groups. Qualitative research leads to the original condition the subject is in. The results of this study have revealed that every dialogue that is displayed has the identity of the Batak tribe that has been created due to infinite things that can transcend human beings and continue to be carried out across generations. This belief is repeated from each generation to be applied to their descendants for every ancestral message, traditional rituals, and history of the Batak community to give identity to selfhood as an individual of the Batak tribe. The conclusion is to find things that are not visible, that do not exist in this program to explain the identity of the Batak people. What transcends the individual into what does not exist is an identity for Batak society. The principle of living with the Batak philosophy, and the consequences of not doing it, is the reason every individual is trapped in having to carry out a culture like it or not as Batak society.